Application of Thoracic Immunogen of Musca domestica on Immunoglobulin-G Level of Goats Detected Through a Single Radial Immuno-Diffusion Test - Laurentius Rumokoy; Wisje Lusia Toar (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
The purpose of this study was to detect the IgG level of goats treated with immunogen thoracic of Musca domestica (ITMd). We reared twelve young goats aged two months old under extensive treatments, divided into two equal groups for a comparison experimental design. The animals in the first group (R0) served as the control without immunogen injection, and the second group (R1) was the treatment group receiving a subcutaneous injection of 10 mL of thoracic antigens per head. The parameter observed was IgG (immunoglobulin-G) antibody serum level. The quantification of goat immunoglobulins was carried out using a single radial immuno-diffusion (SRID) technique. The data obtained from the two groups were analyzed with a t-student test. The results showed that the total IgG antibody serum of goats in the treatment group was significantly higher than that of the control group (P< 0.05). This difference may be due to the thoracic M. domestica immunogen response which increased antibody synthesis of experiment goats. We concluded that the treatment of thoracic immunogen of M. domestica at a level of 10 ÂµL injected subcutaneously could significantly increase IgG antibodies in goat blood which were detected using a single radial immuno-diffusion method.